Opposition between PKC isoforms regulates histone deimination and neutrophil extracellular chromatin release - Radic, Marko; Neeli, Indira (Frontiers in Immunology, 2013)
In response to inflammation, neutrophils deiminate histones and externalize chromatin. Neutrophil extracellular traps (NETs) are an innate immune defense mechanism, yet NETs also may aggravate chronic inflammatory and autoimmune disorders. Activation of peptidylarginine deiminase IV (PAD4) is associated with NET release (NETosis) but the precise mechanisms of PAD4 regulation are unknown. We observed that, in human neutrophils, calcium ionophore induced histone deimination, whereas phorbol myristate acetate (PMA), an activator of protein kinase C (PKC), suppressed ionophore-induced deimination. Conversely, low doses of chelerythrine and sanguinarine, two inhibitors of PKC, reversed PMA inhibition and enhanced ionophore-stimulated deimination. In addition, a peptide inhibitor of PKC  superinduced ionophore activation of PAD4, thus identifying PKC  as the PMA-induced inhibitor of PAD4. At higher doses, chelerythrine, sanguinarine, and structurally unrelated PKC inhibitors blocked histone deimination, suggesting that a different PKC isoform activates histone deimination. We identify PKC  as activator of PAD4 because a specific peptide inhibitor of this PKC isoform suppressed histone deimination. Confocal microscopy confirmed that, in the presence of PMA, NETosis proceeds without detectable histone deimination, and that ionophore cooperates with PMA to induce more extensive NET release. Broad inhibition of PKC by chelerythrine or specific inhibition of PKC  suppressed NETosis. Our observations thus reveal an intricate antagonism between PKC isoforms in the regulation of histone deimination, identify a dominant role for PKC  in the repression of histone deimination, and assign essential functions to PKC  in the activation of PAD4 and the execution of NETosis. The precise balance between opposing PKC isoforms in the regulation of NETosis affirms the idea that NET release underlies specific and vitally important evolutionary selection pressures.